The influence of GSTP1 A313G polymorphism on susceptibility, chemotherapy-related toxicity and prognosis of Hodgkin’s lymphoma in Ukrainian patients - Kriachok, I.A.; Khranovska, N.M.; Svergun, N.M.; Filonenko, K.S.; Novosad, O.I.; Titorenko, I.B.; Martynchik, A.V.; Gubareva, H.O.; Kadnikova, T.V.; Aleksik, O.M.; Kushchevyy, E.V.; Pastushenko, I.V. (Вiopolymers and Cell, 2012)
The aim of this research was to study the influence of GSTP1 A313G polymorphism on susceptibility, chemotherapy-related toxicity and prognosis of Hodgkin’s lymphoma in Ukrainian patients. Methods. The polymorphic variants of GSTP1 gene were analyzed using Allelic Discrimination Real-Time PCR. Results. The GSTP1 polymorphism is not directly involved in the development of Hodgkin’s lymphoma and chemotherapy-related toxicity, but homozygous wild genotype of this gene is associated with a worse clinical response to the therapy and a higher risk of relapse. Conclusions. The investigation of GSTP1 polymorphism is very promising, since it might provide a possible application of this genetic marker as an independent prognostic factor of Hodgkin’s lymphoma.